SIRT1 ameliorates age-related senescence of mesenchymal stem cells via modulating telomere shelterin - Chen, Huiqiang; Liu, Xianbao; Zhu, Wei; Chen, Han; Hu, Xinyang; Jiang, Zhi; Xu, Yinchuan; Wang, Lihan; Zhou, Yu; Chen, Panpan; Zhang, Na; Hu, Dexing; et al. (Frontiers in Aging Neuroscience, 2014)
Age-related mesenchymal stem cells (MSCs) senescence, which impairs its tissue repair capacity in vivo and hence compromises the effects of MSCs-based therapy in clinical applications, is closely related to aging and aging-related diseases. Here, we demonstrated the effect of SIRT1, a NAD+-dependent deacetylase, on age-related MSCs senescence. Knockdown of SIRT1 in young MSCs induces cellular senescence and inhibits cellular proliferation ability whereas overexpression of SIRT1 in aged MSCs reversed the cellular senescence and regained its proliferation capacity, suggesting that SIRT1 could modulate age-induced MSCs senescence. Aging-related proteins, P16 and P21, might be involved in SIRT1-mediated anti-aging effect on MSCs. SIRT1 could positively modulate age-related DNA damage in MSCs. In addition, SIRT1 could induce telomerase reverse transcriptase (TERT) expression and consequently enhance telomerase activity, however, no significant change was observed in telomere length. Moreover, SIRT1 could positively regulate TPP1, an important member of telomere shelterin, expression. Together, these results demonstrate that SIRT1 dampens age-related MSCs senescence, which was correlated with the up-regulation of TPP1 expression, telomerase activity and down-regulation of DNA damage.